X-12y=-62

Simple and best practice solution for X-12y=-62 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-12y=-62 equation:


Simplifying
X + -12y = -62

Solving
X + -12y = -62

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '12y' to each side of the equation.
X + -12y + 12y = -62 + 12y

Combine like terms: -12y + 12y = 0
X + 0 = -62 + 12y
X = -62 + 12y

Simplifying
X = -62 + 12y

See similar equations:

| 0.5=-0.6ln(x)+1 | | y-49=-2 | | 86-2x=6-10x | | 1/x^3=0 | | 0=x-4+3x | | 1/x^3 | | 2xy+3z+1=0 | | x-3-8x-6= | | 5x-2=13x-19 | | 5w^2-30w+40=0 | | 80-5x+4x+10+80=180 | | -6(4y)= | | 6u+6(u-6)=36 | | 4x+10+80-5x=180 | | 13d^2-7d=0 | | -x+17y=127 | | 4(2x-1)-(-3+7)= | | 2y+9=4y-3 | | -1-7x=36x+6(-7-x) | | 4x^4y-36x^3y+80x^2y= | | (17+a)+12= | | x+3=x+11 | | 3z=6z-1 | | 2(-1-3x)=25+3x | | 4M-2(M+6)=5(3M-2)+6 | | 4+4(4x-4)=8-3(2x+1) | | 2y+2=-3 | | 5a-2+3a=17+12a-23 | | x^2-8x+64= | | Y=4Y^2-32Y+65 | | 7(w-8)+7w=14 | | 2x+10+4x-20=180 |

Equations solver categories